2015
DOI: 10.1111/pai.12509
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory allergies in childhood: Recent advances and future challenges

Abstract: The burden of allergic airway diseases still represents a major health problem in childhood. Despite many different options are currently available for the diagnostic work-up and management, the overall disease control in terms of impact on quality of life, morbidity and mortality, is not yet satisfactory. The extreme variability of individual risk factors and severity determinants may account for it. On the other side, the knowledge of the multifaceted allergy background could pave the way to primary preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 110 publications
0
14
0
1
Order By: Relevance
“…Inflammation is the essential part of immune response against pathogens in normal condition. However, excessive inflammation can lead to the onset of inflammatory disease such as atopic dermatitis and asthma [1,3,4,53]. Although further study will be required to investigate the inhibitory effects of 4-chloro-cinnamaldehyde and 4-trifluoro-cinnamaldehyde in vivo, our results of attenuated level of inflammatory mediators clearly indicated that 4-chloro-cinnamaldehyde and 4-trifluoro-cinnamaldehyde may have potential as therapeutic agents against allergic diseases mediated by mast cells based on the mechanism of blocking MKKs-MAPKs signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is the essential part of immune response against pathogens in normal condition. However, excessive inflammation can lead to the onset of inflammatory disease such as atopic dermatitis and asthma [1,3,4,53]. Although further study will be required to investigate the inhibitory effects of 4-chloro-cinnamaldehyde and 4-trifluoro-cinnamaldehyde in vivo, our results of attenuated level of inflammatory mediators clearly indicated that 4-chloro-cinnamaldehyde and 4-trifluoro-cinnamaldehyde may have potential as therapeutic agents against allergic diseases mediated by mast cells based on the mechanism of blocking MKKs-MAPKs signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of allergic diseases, such as atopic dermatitis and asthma, has become an important health problem worldwide, causing poor quality of life in children and adults [1][2][3][4]. Therefore, it is important to identify new therapeutic agents with application in the prevention and treatment of allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The social and economic costs of AR and asthma are impressive, as these diseases heavily influence the patients’ social life, school performance, sleep quality, and psychosocial interactions . Recently, important advances have been reported in the field of respiratory atopic diseases in childhood . This review focuses on recent scientific progress concerning genetic and environmental risk factors, preventive strategies, newest diagnostic tools, and therapeutic opportunities.…”
mentioning
confidence: 99%
“…Looking for a better quality of life (QOL) and disease of overall morbidity and mortality rate seek further investigation on every single individual risk factor that can have even the smallest impact on the disease development. Searching for a new and more individualized treatment for allergic diseases most of current research is focusing on the identification of biological and clinical predictive markers of allergy and asthma onset [9].…”
Section: Epidemiology Of Asthma and Rhinitismentioning
confidence: 99%